Does the RIFLE Classification Improve Prognostic Value of the APACHE II Score in Critically Ill Patients? - Kátia M. Wahrhaftig; Luis C. L. Correia; Denise Matias; Carlos A. M. De Souza (International Journal of Nephrology)
Introduction. The RIFLE classification defines three severity criteria for acute kidney injury (AKI): risk, injury, and failure. It was associated with mortality according to the gradation of AKI severity. However, it is not known if the APACHE II score, associated with the RIFLE classification, results in greater discriminatory power in relation to mortality in critical patients. Objective. To analyze whether the RIFLE classification adds value to the performance of APACHE II in predicting mortality in critically ill patients. Methods. An observational prospective cohort of 200 patients admitted to the ICU from July 2010 to July 2011. Results. The age of the sample was 66 (±16.7) years, 53.3% female. ICU mortality was 23.5%. The severity of AKI presented higher risk of death: class risk (RR = 1.89 CI:0.97–3.38, ), grade injury (RR = 3.7 CI:1.71–8.08, ), and class failure (RR = 4.79 CI:2.10–10.6, ). The APACHE II had C-statistics of 0.75, 95% (CI:0.68–0.80, ) and 0.80 (95% CI:0.74 to 0.86, ) after being incorporated into the RIFLE classification in relation to prediction of death. In the comparison between AUROCs, . Conclusion. The severity of AKI, defined by the RIFLE classification, was a risk marker for mortality in critically ill patients, and improved the performance of APACHE II in predicting the mortality in this population.